2017
DOI: 10.3389/fnsys.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and Decoding Models in Cognitive Electrophysiology

Abstract: Cognitive neuroscience has seen rapid growth in the size and complexity of data recorded from the human brain as well as in the computational tools available to analyze this data. This data explosion has resulted in an increased use of multivariate, model-based methods for asking neuroscience questions, allowing scientists to investigate multiple hypotheses with a single dataset, to use complex, time-varying stimuli, and to study the human brain under more naturalistic conditions. These tools come in the form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 127 publications
(239 reference statements)
1
139
0
Order By: Relevance
“…To test how the brain tracks temporal hazard, we applied an encoding model approach (Lalor et al, 2006, 2009; Naselaris et al, 2011; Mesgarani et al, 2014; Holdgraf et al, 2017) to track temporal hazard in human time-domain EEG, recorded during an auditory foreperiod paradigm (Herbst and Obleser, 2017). The encoding models could distinguish between the different conditions of temporal hazard (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To test how the brain tracks temporal hazard, we applied an encoding model approach (Lalor et al, 2006, 2009; Naselaris et al, 2011; Mesgarani et al, 2014; Holdgraf et al, 2017) to track temporal hazard in human time-domain EEG, recorded during an auditory foreperiod paradigm (Herbst and Obleser, 2017). The encoding models could distinguish between the different conditions of temporal hazard (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The score can be also negative if the model is worse than random guessing. Voxels that had positive variance explained values were identified for further analysis (Miyawaki et al, 2008;Holdgraf et al, 2017) for each participant, ROI and condition. To estimate the empirical chance level performance of the encoding models, a random shuffling was added to the training phase during cross-validation before model fitting.…”
Section: Encoding Model Pipelinementioning
confidence: 99%
“…Moreover, ECoG recordings offer a higher signal‐to‐noise ratio in the fast dynamic signal range above 60 Hz than MEG and EEG recordings (Quandt et al., ). Combining ECoG recordings with statistical modelling techniques recent studies was able to reveal neural mechanisms specific of speech coding in the human brain with high spatial and temporal resolution (Chang et al., ; Holdgraf et al., , ; Mesgarani & Chang, ; Mesgarani, Cheung, Johnson, & Chang, ). Zion Golumbic et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that the two different dynamic bands serve different computational functions in speech processing (Giraud & Poeppel, ). The HG band responses reflect local neural processing (Lachaux, Axmacher, Mormann, Halgren, & Crone, ; Ray & Maunsell, ) and auditory feature processing in primary and higher cortices (Holdgraf et al., , ; Ozker et al., ). The role of LF band activity (from 6 Hz to 30 Hz) in sentence processing might be related to semantic processing (Wang et al., ), disruption of the perceptual status‐quo (Engel & Fries, ) and sentence unification (Bastiaansen, Magyari, & Hagoort, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation